Customer Satisfaction Index of Singapore 2022: National Scorecard - Institute of Service Excellence, SMU (Institutional Knowledge at Singapore Management University, 2022)
This scorecard summarises the results of the CSISG 2022 satisfaction scores at the national, sector, sub-sector, and company levels. CSISG scores are generated based on the econometric modelling of survey data collected from end-users after the consumption of products and services. Company scores (in black) are weighted based on a separate incidence study. This incidence study helps determine each company’s sample profile and the local-tourist weights. Sub-sector scores (in blue) are derived as a weighted average of company scores, in proportion to the local and tourist incidence interactions with the constituent companies. Sector scores (in gold) are derived by aggregating the sub-sector scores proportionately to each sub-sector’s revenue contributions.